INGLIZ TILIDA SUBYEKTIV BAHO MUNOSABATLARI - Husanova Nilufar Saydulloyevna; Mahmudova Nargiza Ravshanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article discusses the definition of subjective evaluation, the views to its approach and the notion of author’s position in literary texts. In addition to this, the following paper presents data related to the methods and means of realizing subjective evaluation in English and Uzbek languages as well as provides practical examples of them.